Assessment of management and outcome of lower respiratory tract infection - Gehan M El Assal; Eman B Abd ElFattah; Nouran A Aref (Egyptian Journal of Chest Disease and Tuberculosis, 2020)
Background Lower respiratory tract infection (LRTI) is an acute disease that is usually presented for 21 days or less. LRTI is a continuous health problem which imposes an enormous burden on the society and is a common reason for out-patient consultation and hospitalization. Patients present with a wide spectrum of symptoms ranging from minor self-limiting illnesses to potentially life-threatening infections. Objective To assess the clinical characteristics, management plan, and outcome of patients with LRTI admitted to Ahmed Maher Educational Tertiary Hospital. Patients and methods This was a prospective study that included 100 patients admitted to the Chest Department at Ahmad Maher Educational Hospital with LRTI from November 2016 till April 2017. LRTI is defined as an acute illness that presents for 21 days or less, usually with cough as the main symptom, with at least one other lower respiratory tract symptom (sputum production, dyspnea, wheeze, or chest discomfort/pain) and no alternative explanation. All patients were subjected to history taking, clinical examination, laboratory investigations, arterial blood gas, sputum analysis, chest radiograph, computed tomography if needed, and Echo if there are signs of heart failure. They were monitored during their hospital stay regarding treatment; oxygen therapy; signs of improvement; complications; outcomes of whether improvement, mortality, or morbidities at discharge; and the length of stay. Results Overall, 69% of patients were male, with mean age of 56.23±11.01 years; 63% were current smokers and 2% ex-smoker, and 6% of the patients were addicts. Leukocytosis was found in 32%, elevated erythrocyte sedimentation rate in 75%, and elevated C-reactive protein in 16% of patients. Overall, 52% had chronic obstructive pulmonary disease with acute exacerbation either alone or associated with other secondary diagnosis, 27% had interstitial lung disease, and 18% had pneumonia. A total of 54 cases presented with respiratory failure. More than half of the patients were treated by monoantibiotic therapy (58%); bronchodilators, either systemic or inhalational, were used in 82% of patients; oxygen therapy was needed in 54%; and 24 patients received systemic steroid. The commonest complication was iatrogenic nausea (60%). The mean length of stay in hospital exceeded 2 weeks, with 99% improvement and discharge rate. Conclusion LRTI is common in our community, and it is closely related to smoking habits. Unfortunately, the nonspecific symptoms delay the diagnosis, yet when managed properly, the outcome is excellent. Combined clinical, laboratory, and radiology assessments help in prompt diagnosis and treatment. The rising percentage of gram-negative organisms is a new challenge, as it adds to the burden of the antibiotic resistance.